Game-based versus multilateral approach: effects of a 12-week program on motor skill acquisition and physical fitness development in soccer school children - Daga, F. A.; Baseggio, L.; Gollin, M.; Beratto, L. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The purpose of this study was to investigate the effects of a 12-week-game-based training versus a traditional multilateral approach on motor skills acquisition and physical fitness, in a group of U9 children playing soccer. METHODS: Forty children aged 9 or younger (U9) recruited from a local soccer school were assigned in a 1:1 ratio to a game-based training program (GB) or a multilateral training (MA) approach. The training programs lasted 12 weeks, and players were tested at baseline and at the end of the program (12-week follow-up). The outcomes were: standing long jump test, shuttle dribble test, 10×5 shuttle run test and Mini-Cooper test. RESULTS: Within-group comparisons showed statistically-significant improvements in both of the groups: standing long lump (P<0.0001), shuttle dribble test (P<0.0001), shuttle run test (P<0.0001) and Mini-Cooper test (P<0.0001). Furthermore, the MA group showed better performance in the shuttle run test after 12 weeks of training compared to the GB group (P=0.0002; +8%). CONCLUSIONS: A multilateral approach promotes physical development in U9 soccer players without affecting learning of-soccer skills. Therefore, a multilateral approach should be included in soccer training programs to ensure an optimal development in young soccer players.